Glucagon-like peptide-1 receptor agonists and the risk of erectile dysfunction: a drug target Mendelian randomization study - An, Hongjin; Xie, Kexin; Gan, Huatian (Frontiers in Endocrinology, 2024)
Background: Glucagon-like peptide-1 receptor agonists (GLP-1RAs) have been widely used for type 2 diabetes (T2D) and weight management. However, the causal relationship of GLP-1RAs with erectile dysfunction (ED) was still unclear. Methods: Mendelian randomization (MR) analysis was conducted to reveal the association of genetically proxied GLP-1RAs with ED. The proportion of potential mediators mediating GLP-1RAs to ED was also assessed by two-step MR. Finally, a series of sensitivity analyses and Two-Sep cis-MR (TSCMR) were performed to evaluate the robustness of the results. Results: MR evidence suggested that genetically proxied GLP-1RAs reduced the risk of ED [odds ratio (OR): 0.493; 95% confidence interval (95% CI): 0.430 to 0.565; P<0.001]. Further mediation analysis via two-step MR showed that this effect was partly mediated through reduced T2D, obesity, hypertension and cardiovascular disease (CVD), with mediated proportions of 2.89% (95% CI:1.28% to 4.49%), 6.83% (95% CI: 2.25% to 11.41%), 3.22 % (95% CI: 1.21% to 5.23%), and 3.06% (95% CI: 0.51% to 5.62%), respectively. Conclusions: GLP-1RAs were associated with a reduced risk of ED, and to a lesser extent, T2D, obesity, hypertension and CVD mediated this effect. Nevertheless, the potential implications of our results for ED prevention policies required validation in further clinical randomized controlled trials.